Spin injection and inverse Edelstein effect in the surface states of topological Kondo insulator SmB6 - Qi Song (Nature Portfolio, 2016)
Spin injection in pure topological surface states of topological insulators is challenging due to the coexistence of highly conducting bulk states. Here, Song et al. report spin injection and inverse Edelstein effect in the spin–momentum locked surface states of topological Kondo insulator SmB6.